Hell to pay : how the suppression of wages is destroying America - Lind, Michael, 1962- (Portfolio/Penguin, an imprint of Penguin Random House LLC, 2023)
"From one of America's leading thinkers, a provocative diagnosis of the cause of America's decline-and a searing indictment of those who caused it For nearly half a century, Americans have been bombarded by neoliberal propaganda promoting the lie that wages are objectively determined by impersonal labor markets. This falsehood has been repeated by academics, journalists, business leaders, and politicians so often that even many on the liberal left and the populist right believe it. In Hell to Pay, Michael Lind, author of The New Class War, debunks this lie. With brutal clarity, he tells the story of how bipartisan political and business interests united to smash the bargaining power of American workers and reduce wages. And with devastating insight he demonstrates that their success has indirectly caused or worsened nearly every symptom of American decline, from the increase in political polarization to the declining birth rate. Calling for a revolution in the way we think about work and wages, Lind argues that the American republic will collapse if worker power is not restored. Fortunately, Hell to Pay doesn't just sound the alarm but also offers a plan for breaking the power of the neoliberal elite and reforming America's disastrous low-wage/high-welfare model-before it's too late"--